The Impact of High-Speed Rail on Residents’ Travel Behavior and Household Mobility: A Case Study of the Beijing-Shanghai Line, China - Hongsheng Chen (Sustainability, 2016)
With the improvement of China’s high-speed rail network, there have been many economic and social benefits for local residents. Based on a questionnaire conducted in stations on the Beijing-Shanghai line, and through an analysis of high-speed rail passenger travel behavior and family relocation, we explored the social effects of high-speed rail. The study found that high-speed rail passengers are mainly young, highly educated, and have a middle to high income. However, with the popularization of high-speed rail, such differences in the social stratum of high-speed rail passengers are expected to disappear. Through an analysis of passenger travel status, we found that the areas surrounding high-speed rail stations are very accessible to the main cities, and are well connected by other public transport. With the emergence of the “high mobility era” based on the high-speed rail network, the separation of workplace and residence and the number of “double city” households are increasing, primarily in the Beijing-Tianjin and Shanghai-Nanjing (especially in Suzhou-Kunshan-Shanghai) regions. In addition, high-speed rail introduces the possibility of household mobility, with 22.7% of the respondents in this study having relocated since the Beijing-Shanghai line opened. Household mobility is apparent primarily among big cities, with movement toward nearby cities. We also found that occupation, income, residence time, and schooling of children have a significant impact on households. With the improvement of high-speed rail networks, household mobility will become a common phenomenon and research on domestic mobility will continue to increase.